The incidence and prevalence of thyroid dysfunction in Europe: a meta-analysis - Garmendia Madariaga, Ane; Santos Palacios, Silvia; Guillén-Grima, Francisco; Galofré, Juan C (The journal of clinical endocrinology and metabolism, 2014)
Thyroid dysfunction is one of the leading endocrine disorders. Previous data show that about half of the population with thyroid dysfunction remains undiagnosed. Our objective was to estimate epidemiologic data on thyroid dysfunction in Europe. PubMed, EMBASE, and SCOPUS databases were searched to identify studies that evaluated the prevalence and/or incidence of thyroid dysfunction in Europe published between 1975 and 2012. Of the 541 identified abstracts examined, 178 were considered for evaluation and 17 were included. Studies were excluded if they included participants with an underlying disease or were limited by age or gender. Results were grouped into 3 categories: 1) prevalence of undiagnosed thyroid dysfunction, 2) prevalence of thyroid dysfunction, and 3) incidence of thyroid dysfunction. Extraction was conducted independently by 2 investigators. An empirical Bayesian random-effects model was used. The prevalence of undiagnosed thyroid dysfunction was assessed in 7 studies with a mean result of 6.71% (95% credibility interval, 6.49%-6.93%): 4.94% (4.75%-5.13%) and 1.72% (1.66%-1.88%) for undiagnosed hypothyroidism and hyperthyroidism, respectively. The prevalence of both previously diagnosed and undiagnosed thyroid dysfunction was assessed in 9 studies with a mean result of 3.82% (3.77%-3.86%): 3.05% (3.01%-3.09%) and 0.75% (0.73%-0.77%) for hypothyroidism and hyperthyroidism, respectively. The incidence rate of thyroid dysfunction was assessed in 7 studies with a mean result of 259.12 (254.39-263.9) per 100 000 per year: 226.2 (222.26-230.17) and 51 (49.23-52.88) per 100 000 per year for hypothyroidism and hyperthyroidism, respectively. This meta-analysis provides extensive data on the prevalence and incidence of thyroid dysfunction in Europe.